2009
DOI: 10.1111/j.1600-0765.2008.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐selectin and L‐selectin polymorphisms in patients with periodontitis

Abstract: The findings of this study showed that the Ser128Arg polymorphism of E-selectin might contribute to the susceptibility of Iranian individuals to periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…To date, eight studies evaluating the association of IL8 SNPs (−251, +396, and +781) and CP or AgP in different populations (mostly in Brazilian but none in the Caucasian population) have been performed, with contradictory results [ 27 32 , 34 , 35 ]. Most of these studies analyzed only the individual SNP and were focused on examining of CP; only Andia et al [ 32 ] studied the relationship between IL8 −251 variant and AgP; however, no association was found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, eight studies evaluating the association of IL8 SNPs (−251, +396, and +781) and CP or AgP in different populations (mostly in Brazilian but none in the Caucasian population) have been performed, with contradictory results [ 27 32 , 34 , 35 ]. Most of these studies analyzed only the individual SNP and were focused on examining of CP; only Andia et al [ 32 ] studied the relationship between IL8 −251 variant and AgP; however, no association was found.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Li et al [ 34 ] found that A allele of IL8 −251 variant was associated with decreased susceptibility to CP in Chinese population. Houshmand et al [ 35 ] found a significant difference in the genotype frequencies of IL8 −251A/T and +396G/T SNPs between subjects with periodontitis and a control group in Hamedan, Iran, but did not specify whether it was for patients with CP or AgP. Conversely, Corbi et al [ 31 ] showed that the genetic susceptibility to CP in the IL8 gene was not associated with worse periodontal clinical parameters and increased IL-8 concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, we had investigated for the potential of a microemulsion based in situ electrolyte-triggered gelling systems for specific delivery of Ciprofloxacin to posterior ocular tissue and fluids. Compared to two other formulations, those are in situ gelling system and eye drop solutions, the Ciprofloxacin microemulsion based in situ gelling system showed better penetration into ocular tissues, higher Ciprofloxacin levels in the vitreous humor, and prolonged residence in the cornea 32 .…”
Section: Discussionmentioning
confidence: 87%
“…CXCR1 and CXCR2 genes and their polymorphisms were reported by four studies 18,24,36,39 . Twenty-two studies focused on IL-8 polymorphisms and their different variants findings 12,[17][18][19][20][21][22][23][25][26][27][28][30][31][32][33]37,40,41,[43][44][45] .…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%